Kinect-Assisted Performance-Sensitive Upper Limb Exercise Platform for Post-stroke Survivors - Dash, Adyasha; Yadav, Anand; Chauhan, Anand; Lahiri, Uttama (Frontiers in Neuroscience, 2019)
One’s ability to use upper limbs is critical for performing activities of daily living necessary for enjoying quality community life. However, after stroke, such an ability becomes adversely affected and it often robs away one’s capability of doing tasks that needs coordinated movement in upper limbs. To address issues with upper limb dysfunction, patients typically undergo rehabilitative exercises. Given the high patient to doctor ratio particularly in developing countries like India, conventional rehabilitation with patients undergoing exercises under one-on-one therapist’s supervision often becomes a challenge. Thus, investigators are exploring technology such as computer-based platforms augmented with cameras that can alleviate the need for continuous presence of therapist and can offer a powerful complementary tool in the hands of the clinicians. Such marker-based imaging systems used for rehabilitation can offer real-time processing and high accuracy of data. However, these systems often require dedicated lab space and high set-up time. Often this is very expensive and suffers from portability issues. Investigators have been exploring marker-less imaging techniques e.g. Kinect integrated computer-based graphical user interfaces in stroke-rehabilitation such as tracking one’s limb movement during rehabilitation. In our present study, we have developed a Kinect-assisted computer-based system that offered Human Computer Interaction (HCI) tasks of varying challenge levels. Execution of the tasks required one to use reaching and coordination skills of upper limb. Also, the system was Performance-sensitive i.e. adaptive to the individualized residual movement ability of one’s upper limb quantified in terms of task performance score. We tested for the usability of our system by exposing 15 healthy participants to our system. Subsequently, 7 post-stroke patients interacted with our system over few sessions spread over two weeks. Also we studied patient’s mean tonic activity corresponding to the HCI tasks as possible indicator of one’s post-stroke functional recovery suggesting its potential of our system to serve as a rehabilitation platform. Our results indicate the potential of such system towards improvement of task performance capability of post-stroke patients with possibilities of upper limb movement rehabilitation.